FACTORS AFFECTING THE MANUFACTURING COMPANIES’ FINANCIAL PERFORMANCE - Syafriont Syafriont (Universitas Hayam Wuruk Perbanas, 2011)
Foreign investment companies have experienced difficulties in improving the financial per- formance. The study aims at explaining the influence of the implementation of information of Management Accountancy towards financial performance of companies. It is an explanatory study in which it applies quantitative approach. The population of the study is three indus- trial manufacturing companies such as PMDN (domestic investment companies) and PMA (foreign investment companies) which are listed in Indonesian Stock Exchange (ISE) in Su- rabaya, East Java, in 2005. These companies are still active until 2009, and they have sub- mitted financial reports annually. The sample consists of 33 companies as the respondents. They are the President Directory of the Companies. Data analysis used to answer the re- search problems and to examine the hypothesis is Structural Equation Modeling (SEM) with the help of Partial Least Square (PLS) program. The result of the study shows, that (1) di- rectly: (a) internal factors influences the implementation of management information of Ac- countancy, (b) internal factors influence the financial performance of companies, (c) the im- plementation of the information of management influences Accountancy the companies' fi- nancial performance. (2) Indirectly: internal factors influence companies 'financial perform- ance through the implementation of the information of Management Accountancy; The find- ing of the study affects the internal factors theoretically and practically through the percep- tion of the companies' organization by involving all employees directly in all activities that supports the improvement of performance ethos of the implementation of accountancy infor- mation and companies' financial performance.